2016
DOI: 10.1177/1745691615621275
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Absolute Moral Opposition to Genetically Modified Food in the United States

Abstract: Public opposition to genetic modification (GM) technology in the food domain is widespread (Frewer et al., 2013). In a survey of U.S. residents representative of the population on gender, age, and income, 64% opposed GM, and 71% of GM opponents (45% of the entire sample) were "absolutely" opposed-that is, they agreed that GM should be prohibited no matter the risks and benefits. "Absolutist" opponents were more disgust sensitive in general and more disgusted by the consumption of genetically modified food than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
284
2
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 220 publications
(308 citation statements)
references
References 43 publications
19
284
2
3
Order By: Relevance
“…Since food is critical for survival, humans developed elaborate food-related behaviors to minimize risks and enhance chances for survival (Rozin, 2001). Following this line of thought, many food- related behaviors are also subject to moral judgment (Lieberman, Tybur, & Latner, 2012; Scott, Inbar, & Rozin, 2016), which is mirrored by the prevalence of food-related taboos across cultures (Meyer-Rochow, 2009) and confirmed both by our behavioral and neuroimaging research. Taking into account that food has not been in surplus for much of human history, the fact that throwing away edible food causes uneasiness is likely to be related to viewing this behavior as reducing fitness, which in turn leads to intuitively judging it as morally disgusting.…”
Section: Discussionsupporting
confidence: 71%
“…Since food is critical for survival, humans developed elaborate food-related behaviors to minimize risks and enhance chances for survival (Rozin, 2001). Following this line of thought, many food- related behaviors are also subject to moral judgment (Lieberman, Tybur, & Latner, 2012; Scott, Inbar, & Rozin, 2016), which is mirrored by the prevalence of food-related taboos across cultures (Meyer-Rochow, 2009) and confirmed both by our behavioral and neuroimaging research. Taking into account that food has not been in surplus for much of human history, the fact that throwing away edible food causes uneasiness is likely to be related to viewing this behavior as reducing fitness, which in turn leads to intuitively judging it as morally disgusting.…”
Section: Discussionsupporting
confidence: 71%
“…This also renders them vulnerable to the naturalistic fallacy, according to which what is natural is equated with being good or desirable, such that when genes are believed to be connected with something bad (such as schizophrenia), the result is viewed less negatively than when people don’t view genes as being involved . The flip side of this is that if genomes are modified through unnatural means, they will tend to be viewed as morally problematic, as genetically modified foods are by many . We are not claiming that the only thoughts that people have about genes are ones that are consistent with these essentialist biases.…”
Section: Genetic Essentialism and Its Vicissitudesmentioning
confidence: 98%
“…Recently, Scott, Inbar, and Rozin () demonstrated that attitudes about GM food are often the result of moral values and intuitions rather than consequence‐based calculations. They asked Americans for their views of the acceptability of GM using a set of questions that have previously been used to measure sacred values (Baron & Spranca, ), including a question that asked whether GM should be prohibited “no matter how small the risks and how great the benefits” (i.e., absolute opposition).…”
Section: Rejection Of Science and Technology On Moral Groundsmentioning
confidence: 99%
“…In other words, in contrast to individuals that are low in disgust sensitivity, individuals who are most likely to express disgust at moral violations (e.g., being hit on by a member of the same sex, or someone who is addicted to drugs), are the most opposed to vaccinations and the most likely to wrongly believe that vaccinations cause autism. The same is true of GM foods—those who are morally opposed to GM foods are more disgust‐prone in general (Scott, Inbar, & Rozin, ). Similarly, pathogen disgust sensitivity is further predictive of mistrust in the safety of vaccines and skepticism of their efficacy, as those who are most likely to express disgust at pathogen exposure (e.g., accidentally touching someone's bloody cut, or stepping in dog poop), are also less likely to believe that vaccinations are effective in protecting against communicable diseases.…”
Section: Rejection Of Science and Technology On Moral Groundsmentioning
confidence: 99%